COMPARATIVE STUDY OF THE CONTENT OF BIOACTIVES COMPOUNDS AND CYANIDIN-3-GLUCOSIDE OF THE PURPLE CORN (Zea mays L.) OF THREE REGIONS OF PERU - Ccaccya Ccaccya, Ana María (2018)
The aim of the research was to evaluate the content of the bioactives compounds in purple corn cob (Zea mays L.) of three differents regions of Peru. The samples were obtained in Lima, Cajamarca and Abancay and the total polyphenols, flavonoids, anthocyanins and cyanidin-3-glucoside content were determined. The extracts were obtained with etanol to 20 %, pH 2, in a ratio of corn cob: solvent 1:100 (p/v) at a temperature of 70 °C for 30 minutes. The results of total anthocyanins were between 24,4 to 42,6 mg/g, the total polyphenols were in the range 67,9 to 94,1 µg/mg expressed as gallic acid equivalent (GAE) and the flavonoids between 3,1 to 4,4 µg/mg expressed as quercetin equivalent (QE). The cyanidin3-glucoside content varied in the range from 9,5 to 18,5 mg/g and was determined by high performance liquid chromatography (HPLC). There are significant differences in the content of the bioactives compounds according to the origin of the sample, and that of Lima (Cañete) present the highest value of polyphenols (94,1 µg GAE/mg), flavonoids (4,4 µg QE/mg) total anthocyanins (42,6 mg/g) y cyanidin-3-glucoside (18,5 mg/g).